Biological pest control in systems of integrated pest management : (Food and fertilizer technology center for the Asia and pacific region, 1996)
This book is the proceedings of an international seminar on the " Use of Biological control Agents under integrated pest management" held in Fukuoka, Japan in October 1993,...